Taxonomic study of the leafhopper genera Farynala Dworakowska and Xaniona Zhang & Huang (Hemiptera: Cicadellidae: Typhlocybinae: Typhlocybini), with descriptions of three new species from China - Yan, Bin; Yang, Mao-Fa (Zootaxa, 2017)
Two new species of the genus Farynala Dworakowska, 1970 and one new species of the genus Xaniona Zhang & Huang, 2005 are described and illustrated: F. dextra sp. nov., F. sinistra sp. nov. and X. falcata sp. nov.. Keys and checklists of genera are provided. The type specimens are deposited in the Institute of Entomology, Guizhou University, Guiyang, China (GUGC).